The Effect of Art Expertise on Eye Fixation-Related Potentials During Aesthetic Judgment Task in Focal and Ambient Modes - Fudali-Czyż, Agnieszka; Francuz, Piotr; Augustynowicz, Paweł (Frontiers in Psychology, 2018)
This study aimed to determine the effect of expertise on the eye fixation-related potentials (EFRPs) during the aesthetic evaluation of images, independently in focal and ambient modes of visual processing. Focal and ambient modes were identified by averaging EFRP waveforms about the beginning of long eye fixations followed by short saccades and short fixations followed by long saccades, respectively. Thirty experts with formal training in visual arts and thirty-two non-experts freely viewed 150 figurative paintings presented for 20 s, each. After viewing the painting, the participant answered the question: “Is this painting beautiful?” Differences were found between the group of experts and non-experts due to the amplitude of EFRPs but only in focal mode, which is related to top-down, focused attention on the objects. Long fixations of experts had a higher amplitude of the parietal P2 recorded from right site than non-experts. In the group of experts, the frontal P2 was higher for long fixations on not beautiful paintings in comparison to long fixation on beautiful paintings. Moreover, in focal mode, there were higher occipital lambda response and N1-P2 complex for not beautiful than beautiful paintings. These results are discussed in the light of the results of studies on the effect of visual art expertise on event-related potentials (ERPs), ERP studies during aesthetic judgment task, and the knowledge of different modes of visual processing and EFRPs.